Influence of Guidance and Counselling Services on Academic Performance of Students in Rwanda Universities: Case Study of the University of Kigali and the University of Rwanda - Patrick Adekulay Sylvanus Maxwell; Abdulrazaq Olayinka Oniye (Researchparks Publishing, 2022)
The purpose of the study was to investigate the influence of Guidance and Counselling services on the academic performance of students in Rwanda universities using the Universities of Rwanda and the University of Kigali as the case studies. The rationale was to understand whether there is a relationship between G&C services and academic performance based on the perception of the students. Four research objectives were formulated to guide this study, to assess the influence of G&C services on university students' academic performance; to determine the relationship between G&C services and university students’ academic performance in Rwanda, to evaluate the effectiveness of the G&C programme in Rwanda universities in relation to students’ academic performance, and to access the impacts of parental involvement in G&C services on students’ academic performance. The study employed a descriptive essay design. The sample size was 395 respondents out of 32,345. The study findings revealed that: the respondents when answering the questions on the influence of G&C where at a moderate level with the mean scores of 3.17, 3.38, 3.31, 3.46, 3.12, 3.35 and 3.37 respectively, on the effectiveness of G&C respondents where at a moderate level with the mean scores of 3.6, 3.07, 3.26, and 3.27 respectively, on the Parental Involvement respondents where at a moderate level with the mean scores of 2.58, 3.21, 2.95, 2.58 and 2.83 respectively and on students’ academic performance respondents where at a moderate level with the mean scores of 3.34, 3.43, 3.19, and 3.48 respectively. There is a positive relationship between G&C Services and students’ academic performance on universities students (.863). It was therefore recommended that through the Ministry of Education and Higher Education Council in Rwanda, the universities have to allocate more funds to G&C centers to obtain more practical G&C service from appropriate professionals in G&C.